The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1007/s11832-011-0364-0
|View full text |Cite
|
Sign up to set email alerts
|

Transtibial Ertl amputation for children and adolescents: A case series and literature review

Abstract: Our results suggest that the Ertl osteomyoplasty is a feasible option in this challenging patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Pellicore et al observed bone growth stimulation following amputation and concluded that stump overgrowth occurs because soft tissues cannot keep up with the rapid growth of the bone [16]; however, attempts to treat overgrowth by proximal epiphysiodesis and leaving long redundant soft tissue have failed [12,[17][18][19]. The incidence of the overgrowth phenomenon in cases of surgical and post-trauma amputations was higher [1][2][3]5] compared with that of disarticulation amputation and congenital agenesis, [7,20] which suggests that stump overgrowth might be a result of bone and soft tissue trauma rather than continuous growth of the proximal physis. This would mean that overgrowth is a local Stump Overgrowth after Limb Amputation in Children DOI: http://dx.doi.org /10.5772/intechopen.90532 process of bone formation and wound healing that occur in the distal stump.…”
Section: Pathogenesismentioning
confidence: 99%
“…Pellicore et al observed bone growth stimulation following amputation and concluded that stump overgrowth occurs because soft tissues cannot keep up with the rapid growth of the bone [16]; however, attempts to treat overgrowth by proximal epiphysiodesis and leaving long redundant soft tissue have failed [12,[17][18][19]. The incidence of the overgrowth phenomenon in cases of surgical and post-trauma amputations was higher [1][2][3]5] compared with that of disarticulation amputation and congenital agenesis, [7,20] which suggests that stump overgrowth might be a result of bone and soft tissue trauma rather than continuous growth of the proximal physis. This would mean that overgrowth is a local Stump Overgrowth after Limb Amputation in Children DOI: http://dx.doi.org /10.5772/intechopen.90532 process of bone formation and wound healing that occur in the distal stump.…”
Section: Pathogenesismentioning
confidence: 99%
“…If we can impart a greater potential of these periosteal cells to proliferate to a similar extent to that of the PP cells through a means of dedifferentiation/reprogramming (Takahashi and Yamanaka, 2006) or transdifferentiation (Thorel et al, 2010), we might be able to realize the dream of regenerating limbs in humans. Indeed, an overgrowth of bone over the limb stump sometimes occurs in subjects after an amputation transects the long bone (Firth et al, 2011). This phenomenon occurs most commonly in children under 12 years of age, but never after a person reaches skeletal maturity, which indicates that as long as the periosteal cells of the long bone possess the ability to proliferate, they would be able to extend a stump further.…”
Section: Lessons Learnt From Antler For Regenerative Medicinementioning
confidence: 99%
“…Data is limited, and results have been mixed. 19,20 Firth and colleagues treated four patients with the Ertl procedure. One of the four cases required revision for stump overgrowth.…”
Section: End Bearing Residuummentioning
confidence: 99%